Deficyt biotynidazy a narząd wzroku - Mrugacz, Małgorzata; Bakunowicz-Łazarczyk, Alina; Średzińska-Kita, Dorota (Klinika Oczna / Acta Ophthalmologica Polonica, 2002)
Biotinidase deficiency is an autosomal recessive disorder depending on the deficiency of 4 biotin-containing carboxylases. This disease can lead to variety of neurologic, ophthalmolgic and cutaneous symptoms, when untreated.